The inquisition / 2 - Matharu, Taran (Matharu, Taran. Summoner, 2016)
Fletcher is put on trial by the Inquisition where he discovers his tragic origins, then is sent by the king into the Orc jungles where he and loyal friends Othello and Sylva must battle their way to the heart of Orcdom and save Hominum from destruction.